Uncovering the heterogeneity of the gut microbial taxa associated with the contents of different fatty acids in muscle with cecum luminal content and fecal samples from two pig populations - Sun, Xiao; Yang, Bin; Chen, Congying (Frontiers in Microbiology, 2025)
Fatty acids in pork are involved in cellular physiological functions and related to meat nutrition, tenderness, and flavor. Increasing evidences have suggested that short-chain fatty acids produced by the gut microbiota may affect host metabolism and energy utilization. However, the association between gut microbiota and long-chain fatty acids (LCFAs) in pork has been largely unknown. In this study, the microbial compositions of 243 cecum content samples from Erhualian pigs and 235 fecal samples from Bamaxiang pigs were determined by high throughput 16S rRNA gene sequencing. The contents of 12 LCFAs in longissimus dorsi (LD) muscle were also determined for all experimental pigs of both pig populations. We systematically evaluated the contribution of gut microbiota to the variations of muscle fatty acid contents from the α-diversity of gut microbiota, co-abundance groups (CAGs) of Amplicon Sequence Variants (ASVs), and fatty acid-associated bacterial taxa. We identified hundred ASVs and > 40 bacterial taxa that were significantly associated with muscle fatty acid contents in two pig populations. Different numbers and bacterial taxa associated with the content of specific LCFAs in muscle were detected between cecum luminal content and fecal samples, suggesting the heterogeneity of the specific LCFA-associated bacterial taxa between two gut locations. We uncovered some interesting associations between bacterial taxa and muscle fatty acid contents. The strongest association was observed between the ASV annotated to Akkermansia and the n-6/n-3 polyunsaturated fatty acid ratio (p = 6.45E-04, Z = −9.65). The gut microbiota could explain 1.47–4.62% variation of muscle contents of twelve fatty acids. The functional prediction analysis identified that the KEGG pathways related to the metabolisms of carbohydrate and lipids, and to fat digestion and absorption were positively associated with the contents of muscle fatty acids. However, adipocytokine signaling pathway and thermogenesis were negatively associated with muscle fatty acid contents. The results from this study provided the basic knowledge for improving the muscle fatty acid contents by regulating the gut microbiome.